ENVIRONMENTAL EDUCATION (ECO EDUCATION) IN THE FAMILY THROUGH THE KANG PISMAN MOVEMENT - Novia Ekawati; Ance Cahyati (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
Waste problems that occur in large urban communities, such as the city of Bandung, need to be taken seriously because waste problems are not only a problem of cleanliness and the environment, but can also be a conflict of social problems in the community. The family as the smallest community in the community structure is the source of the waste problem itself with the largest contribution to piles of waste originating from household waste. The Bandung city government has launched the Kang PisMan movement as a flagship program in alternative waste management in the city of Bandung as an effort to make Bandung a waste-free area. The purpose of this research is to study the extent to which the Kang PisMan movement as a Bandung city government program has been recognized by the community and can be an alternative environmental education in the family that can contribute to waste management, especially in the city of Bandung. The research method used is quantitative and qualitative methods through surveys, interviews, and direct observation. The results of this study are expected to build public awareness of the importance of environmental education starting with the family, one of which is by supporting the Kang PisMan movement. AbstrakPermasalahan sampah yang terjadi pada masyarakat kota besar, seperti kota Bandung perlu ditangani secara serius karena permasalahan sampah bukan hanya menjadi permasalahan kebersihan dan lingkungan hidup, namun juga bisa menjadi konflik permasalahan sosial di masyarakat. Keluarga sebagai komunitas terkecil dalam tatanan masyarakat adalah sumber dari permasalahan sampah itu sendiri dengan adanya kontribusi terbesar pada timbunan sampahoyang bersumberidari sampahirumah tangga. Pemerintah kota Bandung mencanangkan gerakan Kang PisMan sebagai program unggulan dalam altenatif penanganan sampah di kota Bandung sebagai upaya mewujudkan kota Bandung sebagai kawasan bebas sampah. Penelitian ini bertujuan untukmengetahui sejauh mana gerakan Kang PisMan sebagai program pemerintah kota Bandung telah diketahui oleh masyarakat dan bisa menjadi salah satu alternatif pendidikan lingkungan hidup dalam keluarga yang bisa memberikan kontribusi pada pengelolaan sampah, khususnya di kotaiBandung. Metodeipenelitian yangidigunakan adalahimetode kuantitatif dan kualitatif melalui survei, wawancara, dan observasi langsung. Hasil dari penelitian ini diharapkan dapat membangun kesadaran masyarakat akan pentingnya pendidikan lingkungan hidup yang dimulai dari keluarga, salah satunya adalah dengan mendukung gerakan Kang PisMan.